Losing touch. Issue 3 (22nd July 2020) - Nist, Marliese Dion; Harrison, Tondi M.; Tate, Judith; Robinson, Audrey; Balas, Michele; Pickler, Rita H.
Abstract: The need for human touch is universal among critical care patients and is an important component of the nurse–patient relationship. However, multiple barriers to human touch exist in the critical care environment. With little research to guide practice, we argue for the importance of human touch in the provision of holistic nursing care.